1999
DOI: 10.1007/s004410051368
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of intrinsic cardiac neurons in whole-mount guinea pig atria identified by multiple neurochemical coding

Abstract: Functional data indicate that neurons in distinct regions of the heart exert preferential regional cardiac control. To date the regional distribution of specific types of neurons within the intrinsic cardiac nervous system remains unknown, as does their associations with distinct neurotransmitter and/or neuromodulatory profiles. This study was designed to ascertain: (1) the distribution of different classes of neurons within the intrinsic cardiac nervous system as determined by microscopic analysis; (2) the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 26 publications
1
56
1
Order By: Relevance
“…In vertebrates, the intrinsic cardiac nervous system exhibits a range of different morphological and immunohistochemical properties (Holmgren et al 1994, Horackova et al 1999, Kuncova et al 2003. Blood pressure and heart rate are regulated by circulating neuropeptides which involve the brain-cardiac axis (Xiang 1994, Matsumara et al 2003, Pedrazzini et al 2003 and by endogenous molecules synthesised by heart neurons (Lillywhite et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In vertebrates, the intrinsic cardiac nervous system exhibits a range of different morphological and immunohistochemical properties (Holmgren et al 1994, Horackova et al 1999, Kuncova et al 2003. Blood pressure and heart rate are regulated by circulating neuropeptides which involve the brain-cardiac axis (Xiang 1994, Matsumara et al 2003, Pedrazzini et al 2003 and by endogenous molecules synthesised by heart neurons (Lillywhite et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…This is also confirmed by the results of a study by Hardwick et al [21], who found two types of neurons in the cardiac ganglia of guinea pigs: phasic, constituting about 95%, and tonic (the remaining 5%). Horackova et al [30] also found two morphological types of neurons: about 80% of large neurons, 15-40 µm in diameter, and about 20% of the so-called small neurons. Moreover, the authors demonstrated the presence of three cell subpopulations varying in neurochemical properties.…”
Section: Morphology Of Cardiac Gangliamentioning
confidence: 93%
“…Immunohistochemical studies of Horackova et al [30] on the intracardiac ganglia of guinea pigs showed that ganglionic neurons can be divided into three subpopulations differentiated by size and the expression of various transmitters. About 80% of neurons located in ganglia had large diameters of up to 40 µm, and about 15% had small diameters below 15 µm.…”
Section: Neurochemical Characteristic Of Cardiac Gangliamentioning
confidence: 99%
See 2 more Smart Citations